Impact of sub-eutectoid thermal aging on martensitic transformation, thermo-structural properties, and gamma-neutron shielding performance of CuAlMnFe high-temperature shape memory alloy - Karaduman, Oktay; Kalay, Ece; Ozkul, Iskender; Kurgun, Mehmet Ali; Canbay, Canan Aksu; Guler, Omer; Tekin, H. O. (Springer, 2025)
A novel Cu-based high-temperature shape memory alloy (HTSMA) with the composition 70.84Cu-23.80Al-4.14Mn-1.22Fe (at. %) was successfully synthesized via arc melting in this study. The effects of thermal aging duration on the alloy's martensitic transformation behavior, shape memory effect (SME), and microstructural evolution were systematically investigated. Six samples were prepared from the as-cast ingot: one was homogenized in the beta-phase region and quenched into ice-brine to induce a martensitic structure, while five others were subsequently aged at 350 degrees C for varying durations and air-cooled. Thermal and structural characterizations were conducted. These included differential scanning calorimetry (DSC), X-ray diffraction (XRD), energy-dispersive spectroscopy (EDS), and optical microscopy. Prolonged aging altered transformation temperatures and reduced both enthalpy and entropy values. It also promoted the formation of observed precipitates, vacancies, and coarsened 2H martensites. Prolonged aging altered the microstructure and thermal response, leading to partial SME degradation. Additionally, the alloy's gamma-ray and fast neutron shielding parameters were theoretically estimated using simulation software to explore its potential functional scope. The calculated results indicate that the CuAlMnFe HTSMA is predicted to exhibit favorable attenuation performance across a wide energy spectrum, with appropriate values of mass attenuation coefficient (MAC) and half-value layer (HVL). In particular, the fast neutron removal cross-section was calculated as 0.139 cm-1, which is significantly higher than those of water (0.1023 cm-1), graphite (0.0773 cm-1), and B4C (0.0714 cm-1). In conclusion, the CuAlMnFe HTSMA developed in this study offers a unique profile combining tailorable shape memory behavior with a computationally predicted potential for nuclear radiation shielding. These properties offer novel insights into the alloy's potential for applications in high-radiation environments that require both mechanical actuation and radiation protection, pending experimental validation of its shielding performance.
Keywords: Mass Attenuation; Grain-Refinement; Phase-Stability; Cu-Zn; Microstructure; Parameters; Radiation; Texture; Entropy; Element